Permasalahan Aktivitas Pembelajaran Matematika Sekolah Dasar Selama Era New Normal - Imanuel Yosafat Hadi Manapa (SAP (Susunan Artikel Pendidikan), 2021)
Elementary school math learning activities during the new normal era in Alor District are conducted online, home visits, and shifting. This is a transformation of learning activities that are situational and relatively new in this district. The purpose of this study is to explore the problems encountered from all three mathematical learning activities during the new normal era. This research practiced a qualitative research method with a case study approach. The informants in this study were nine teachers determined by using purposive sampling techniques. The informants came from three schools with different learning activities. Data collection was carried out in January 2021. There were several learning problems found during new normal era, namely the competence of teachers and parents in terms of the use of online learning technology, learning design, learning evaluation, student readiness, and the active role of parents. Based on the findings in this study, alternative solutions were provided to minimize various mathematical learning problems during the new normal era.